PENGEMBANGAN TES DIAGNOSTIK UNTUK MENGIDENTIFIKASI MISKONSEPSI PESERTA DIDIK MATERI GETARAN DAN GELOMBANG KELAS VIII - Nur Af idah,; Haratua Tiur Maria S; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study was aimed to produce a diagnostic test in the form of multiple-choice to distinguish students’ misconceptions on the subject material vibration and waves at Junior High School Level. This study was conducted in the form of a research and development (R&D) comprising (1) preparation of test specifications which include determination of test objectives, preparation of test lattices, determination of test forms, determination of test length, (2) writing of test items, (3) checking of test items, (4) testing of tests, (5) analysis of test items, (6) improvement of test items, (7) test assembly, (8) test implementation involving students from SMPN 1 MempawahHilir and MTs Muhammadiyah Bakau Kecil, and (9) interpretation of test results. The results of the analysis showed that the developed test was based on the students’ initial conception of the vibration and waves subject from the previous research. After being tested, the product obtained validity by 0.76, reliability by 0.76, readability by 4.2, and difficulty level by 0.44. Therefore, as the product met the characteristic of the test, the diagnostic test was valid and reliable to use, of which the readability and level of difficulty were equivalent to the level of the students. This research expected to be used as reference for further research. Keywords: Development, Diagnostic Test,Vibrations and Waves